Pengaruh Self Image dan Penerimaan Sosial terhadap Kepercayaan Diri Remaja yang Mengunggah Foto Selfie di Media Sosial Instagram - Selviana Selviana; Sari Yulinar (Universitas Persada Indonesia YAI, 2022)
The purpose of this study was to determine the effect of self-image and social acceptance onself-confidence in adolescents who upload selfie photos on Instagram social media. Thesampling method used was convenience sampling. Respondents of this study are followers whofollow the researcher's Instagram account with a sample of 108 teenagers. This researchinstrument uses three Likert scale models, namely: self-confidence scale, self image scale, andsocial acceptance scale. The data analysis technique used is linear regression. The results ofthe self-image hypothesis test on self-confidence obtained the value of the t-count coefficient of10.850 and p of 0.000; (p < 0.05) then H01 is rejected and Ha1 is accepted. Meanwhile, socialacceptance of self-confidence is obtained by the t-count coefficient of 7.479 and p of 0.000; (p< 0.05) then H02 is rejected and Ha2 is accepted. The calculated F value is 86,857 and p is0.000; (p) < 0.05. H03 is rejected and Ha3 which reads that there is an influence of self imageand social acceptance on the self-confidence of teenagers who upload selfie photos onInstagram social media is accepted.